Secular trends in the prevalence of type 2 diabetes in adults in China from 1995 to 2014: A meta‐analysis: 1995‐2014年中国成人2型糖尿病患病趋势的meta分析摘要. (22nd August 2016) - Han, Chengyi; Zhang, Ming; Luo, Xinping; Wang, Chongjian; Yin, Lei; Pang, Chao; Feng, Tianping; Ren, Yongcheng; Wang, Bingyuan; Zhang, Lu; Li, Linlin; Yang, Xiangyu; et al.
Abstract: Background: The aim of the present study was to estimate trends in the prevalence of type 2 diabetes mellitus (T2DM) in adults in China. Methods: A systematic search was conducted for studies of T2DM prevalence in adults in China from 2000 to 2014. Pooled prevalence was calculated by a random‐effects model. Subgroup and sensitivity analyses were performed. Chi‐squared and Cochran–Mantel–Haenszel tests were used to assess differences among subgroups and pooled prevalence, respectively. Results: Forty‐six studies (data from 1995 to 2014; 1 463 079 adults) were included in the meta‐analysis. The overall prevalence of T2DM was 7.9 %. The pooled prevalence overall and by location (urban and rural), gender (male and female), and age category (18–39, 40–59, and ≥60 years) was 4.5 %, 5.1 % and 3.0 %, 4.0 % and 4.2 %, and 1.4 %, 5.0 %, and 10.3 %, respectively, from 1995 to 1999; 6.6 %, 9.3 % and 5.6 %, 7.4 % and 7.5 %, and 1.8 %, 5.9 %, and 12.4 %, respectively, from 2000 to 2004; 10.3 %, 11.8 % and 6.8 %, 10.0 % and 8.6 %, and 2.8 %, 10.3 %, and 20.0 %, respectively, from 2005 to 2009; and 8.3 %, 12.5 % and 7.6 %, 8.6 % and 8.0 %, and 3.5 %, 8.5 %, and 15.3 %, respectively, from 2010 to 2014. The prevalence increased from 5.8 % to 11.6 % with per‐capita gross domestic product and differed by diagnostic criteria. Conclusions: There was a trend of increasing prevalence of T2DM in adults in China from 1995 to 2009, with a decrease in 2010–14 and a greater increase over time in urban versus rural areas, males versus females, and older versus younger adults. Highlights: There was a trend for increased prevalence of T2DM in adults in China from 1995 to 2009, with a decrease from 2010 to 2014. The increase in the prevalence of T2DM was greater for urban than rural areas, males than females, and older than younger adults. Higher prevalence was observed in urban than rural populations, older than younger adults, and high AGDP than low AGDP areas. Comprehensive and specific prevention interventions should be taken to respond to the emerging diabetes epidemic in China. Trends in the prevalence of type 2 diabetes mellitus (1995–2014). Each symbol represents the time‐specific prevalence rates from one study of the adult population from mainland China: (a) Overall prevalence; (b) prevalence in urban (●) and rural (▪) regions; (c) prevalence in men (●) and women (▪); and (d) prevalence in different age groups (●, ≥60 years; ▪, 40–59 years; ⧫, 18–39 years). Open squares represent the time‐specific pooled prevalence rates for included studies, with whiskers indicating 95 % confidence intervals: (a) overall; (b) pooled prevalence rates for urban (red) and rural (blue) regions; (c) pooled prevalence rates for men (red) and women (blue); and (d) pooled prevalence rates for those aged ≥60 years (red), 40–59 years (blue), and 18–39 years (green).